Approximate Cubic Lie Derivations on ρ-Complete Convex Modular Algebras. (1st October 2018) - Kim, Hark-Mahn; Shin, Hwan-Yong
Abstract : In this article, we present generalized Hyers–Ulam stability results of a cubic functional equation associated with an approximate cubic Lie derivations on convex modular algebrasχ ρ withΔ 2 -condition on the convex modular functionalρ .